2013
DOI: 10.1530/joe-13-0388
|View full text |Cite
|
Sign up to set email alerts
|

Role of sphingolipids in oestrogen signalling in breast cancer cells: an update

Abstract: The signaling pathways activated by the steroid hormone oestrogen include a variety of cytoplasmic second messengers linked to a multitude of tissue-specific effects. In the last decade, sphingolipids and their membrane receptors were added to the list of oestrogenactivated mediators. Oestrogen triggers the sphingolipid signalling cascade in various tissues including breast cancer. Extensive research has shown that sphingolipids are the key regulatory molecules in growth factor networks. Sphingolipids can cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 79 publications
2
30
0
Order By: Relevance
“…The prediction of starch and sucrose metabolism confirms previous genome-wide association studies, which reported significant relation between altered starch and sucrose pathway and the risk of developing ER-negative breast cancer [47]. Sphingolipids are responsible for oestrogen signaling and can control differentiation and proliferation of breast cancer cells [48]. The glycerophospholipid pathway, also flagged as biomarker by GEMsplice, was previously found altered in the metabolic phenotype of breast [49].…”
Section: Pathway-based Flux Analysissupporting
confidence: 84%
“…The prediction of starch and sucrose metabolism confirms previous genome-wide association studies, which reported significant relation between altered starch and sucrose pathway and the risk of developing ER-negative breast cancer [47]. Sphingolipids are responsible for oestrogen signaling and can control differentiation and proliferation of breast cancer cells [48]. The glycerophospholipid pathway, also flagged as biomarker by GEMsplice, was previously found altered in the metabolic phenotype of breast [49].…”
Section: Pathway-based Flux Analysissupporting
confidence: 84%
“…Dietary agents also synergize with chemotherapeutic drugs, thereby reducing the dose of treatment and their whole body toxicity (6)(7)(8)(9). Several dietary compounds such as curcumin (6), genistein (10), dietary isothiocyanates (11), silibinin (8), and the grape fruit contained polyphenol resveratrol (7,(12)(13)(14)(15)(16)(17)(18)(19) have been shown to block the cell cycle in tumoral cells, counteracting the dysregulation of proliferation that is a hallmark in all types of cancer.…”
Section: Natural Grape Extracts Regulate Colon Cancer Cells Malignancymentioning
confidence: 99%
“…There is substantial evidence obtained in human and animal studies indicating that certain bioactive sphingolipids are involved in development and progression of cancer [7][8][9][10][11][12]. Sphingolipids are a group of lipids containing an organic aliphatic amino alcohol sphingosine backbone or a substance structurally similar to it.…”
Section: Introductionmentioning
confidence: 99%